Development of Yuk Bariya Comic based on Toyomarto Village Wisdom for Folklore Learning - Taufiqqurrohman Taufiqqurrohman; Putri Kumala Dewi (Jurnal Pendidikan Edutama, 2024)
The instructional media used in online learning for reading folklore lacks variety. Additionally, folklore derived from the cultural wisdom of the surrounding area has not been utilized in teaching folklore reading and remains unknown to learners. In response to these issues, learners require more diverse instructional media that can incorporate folklore from Toyomarto Village. This research aims to develop instructional media based on the wisdom of Toyomarto Village for teaching folklore reading in terms of content appropriateness, language, and presentation systematics. This development research employs the ADDIE model. The results of this research, including validation tests for content appropriateness, language, presentation systematics, practitioner evaluation, and small- and large-scale trials, all received a 'very good' category. The final percentage for each test was 96.88%, 92.86%, 100%, 98.39%, and 88.12%, as well as 85.12%. Based on the validation and product testing results, Yuk Bariya comic is deemed suitable for teaching folklore reading.